Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/bot.0b013e31812e5186
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of the Saline Load Test in the Diagnosis of Traumatic Knee Arthrotomies

Abstract: For small lacerations around the knee, saline loads of less than 194 mL are of questionable sensitivity, and surgeons should not use the saline load test to rule out open knee injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 1 publication
0
32
0
Order By: Relevance
“…The observed wide range of the knee volume (40-290 ml) explains the low sensitivity and specificity of the saline load test that is used to determine a traumatic capsule defect [9][10][11][12]. This problem limits the diagnostic value of the saline load test with reported cut-off values between 60 and 194 ml [9][10][11][12].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The observed wide range of the knee volume (40-290 ml) explains the low sensitivity and specificity of the saline load test that is used to determine a traumatic capsule defect [9][10][11][12]. This problem limits the diagnostic value of the saline load test with reported cut-off values between 60 and 194 ml [9][10][11][12].…”
Section: Discussionmentioning
confidence: 93%
“…This problem limits the diagnostic value of the saline load test with reported cut-off values between 60 and 194 ml [9][10][11][12].…”
Section: Discussionmentioning
confidence: 95%
“…1 In addition, a saline load test may be used to help in diagnosis and determine whether or not to proceed with surgical intervention. 3 The saline load test is performed by injecting sterile saline into a joint and then examining the joint for evidence of fluid leakage at rest and with passive movement. Fluid leakage from the joint indicates a positive test.…”
mentioning
confidence: 99%
“…The detection rate in these studies is between 36% and 46% at clinically accepted volumes of 50 to 60 mL. [4][5][6] Our rate was only 33% at 180 mL, whereas other studies had an improved sensitivity in the 90% to 99% range at this volume. Nord et al used a dynamic test by putting the knee through a range of motion during injection, which may have accounted for their improved sensitivity at higher volumes (99% at 175 mL).…”
Section: Discussionmentioning
confidence: 69%
“…Keese et al found that a saline load of 194 mL was required to achieve 95% sensitivity for the test and a similar study by Nord et al found an only slightly better 155 mL was required for 95% detection rate. 4,5 Tornetta et al also found that injecting knees with a known arthrotomy with 60 mL of normal saline yielded a very low sensitivity. 6 The common theme among these studies is that the saline load test is not reliable for ruling out an open intra-articular knee injury.…”
Section: Introductionmentioning
confidence: 96%